Fruit quality of Tahiti acid lime and Sicilian lemon trees grown on different rootstocks and spacings in the semi-arid region - Almeida, Lucicleia Borges de; Pereira, Marlon Cristian Toledo; Bastos, Débora Costa; Pimenta, Samy; Pinheiro, Juceliandy Mendes da Silva; Nietsche, Silvia (Comunicata Scientiae, 2021)
The objective of this work was to evaluate the fruit quality of Tahiti acid lime and Sicilian lemon trees grown on different rootstocks and planting spacings in the semi-arid region of the state of Minas Gerais, Brazil. Two experiments were conducted, using Tahiti acid lime tree scions (Citrus latifolia Tanaka) (1) and Sicilian lemon trees scions [Citrus limon (L.) Burm] (2). A randomized block design was used, with a 6×2 factorial arrangement consisted of six rootstocks: Cravo Santa Cruz lemon (Citrus limonia Osbeck), Swingle citrumelo [Citrus paradisi Macfaden × Poncirus trifoliata (L.) Rafinesque], Indio citrandarin and Riverside citrandarin [Citrus sunki (Hayata) hort. ex Tanaka × Poncirus trifoliata (L.) Rafinesque], Hybrid TSKC × (LCR × TR) - 059 [Citrus sunki (Hayata) hort. ex Tanaka × (Citrus limonia Osbeck × Poncirus trifoliata (L.) Rafinesque)], and Sunki Tropical tangerine [Citrus sunki (Hayata) hort. ex Tanaka]; and two planting spacings: 6.0 × 4.0 m and 6.0 × 2.0 m, with three replications and four plants per plot. The physical and chemical characteristics of fruits were evaluated. Most quality characteristics of Tahiti acid lime and Sicilian lemon are not affected by the different rootstocks and spacings used, but the fruits present excellent quality for the national and international markets. Tahiti acid lime plants grown on less vigorous rootstocks under denser spacings have fruits with higher pH, whereas those grown on more vigorous rootstocks have fruits with thicker mesocarps and lower soluble solid contents. The use of Sunki Tropical tangerine rootstock results in bigger Sicilian lemons, however, with lower soluble solid contents, whereas an opposite result is found with the use of Swingle citrumelo rootstocks.